Navigating Regional Regulatory Changes in Indonesia: An In-Depth Analysis of Post-Amendment Implementation of Law Number 12 of 2011 on Legislation Formation - Bayangsari Wedhatami; Ratih Damayanti; Cindy Ayu Prasasi (Universitas Negeri Semarang, 2023)
In the context of Indonesia as a State of Law, the imperative role of the rule of law cannot be overstated in realizing the state's objectives. The formulation of Legislative Regulations, essential for upholding the rule of law, necessitates meticulous consideration of three fundamental principles: benefit, justice, and legal clarity. To ensure the effectiveness of these regulations in aligning with the direction and goals of national legal development, the process adheres to key principles, encompassing the clarity of objectives, appropriate institutional involvement, congruence among types, hierarchy, and material content, practicability, clarity of formulation, and transparency. This procedural framework is consistently implemented in a sustainable, coordinated, and integrated manner. The legal landscape in Indonesia underwent significant transformations with the enactment of Law Number 11 of 2020 on Job Creation, introducing the omnibus law technique. However, the subsequent Constitutional Court Decision Number 91/PUU-XVIII/2020 provisionally deemed this law unconstitutional. Responding to this decision, Law Number 12 of 2011 underwent a substantial amendment through Law Number 13 of 2022, specifically addressing the omnibus approach and enhancing meaningful public participation in statutory rule creation. This legal revision significantly influences the development of legal instruments at the regional level. Consequently, an examination of the implementation of regional legal product formation becomes imperative post the amendment of Law Number 12 of 2011 on the Formation of Legislative Regulations.